2005
DOI: 10.1086/429595
|View full text |Cite
|
Sign up to set email alerts
|

Cataclysmic Variables from Sloan Digital Sky Survey. IV. The Fourth Year (2003)

Abstract: This paper continues the series presenting cataclysmic variables identified during the fourth year (2003) of the Sloan Digital Sky Survey. We describe 44 close binary systems, of which 12 are the previously known systems EN Cet, EG Cnc, V844 Her, GG Leo, Leo 7, CY UMa, DV UMa, EK UMa, EV UMa, UMa 8, EUVE J0854+390, and RX J0859.1+0537 and 32 are new cataclysmic variables. As in the previous papers, the positions, colors, and spectra of all 44 systems are shown, along with follow-up spectroscopic, photometric, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(167 citation statements)
references
References 27 publications
8
158
0
Order By: Relevance
“…It is not clear why eclipses were not detected by Szkody et al (2005), although it must be remembered that the telescope available to these authors was much smaller (1.0 m versus 3.6 m). Dr. A. Henden (private communication) has kindly supplied the data from Szkody et al for a closer inspection.…”
Section: Sdss J09244448+0801509mentioning
confidence: 89%
See 2 more Smart Citations
“…It is not clear why eclipses were not detected by Szkody et al (2005), although it must be remembered that the telescope available to these authors was much smaller (1.0 m versus 3.6 m). Dr. A. Henden (private communication) has kindly supplied the data from Szkody et al for a closer inspection.…”
Section: Sdss J09244448+0801509mentioning
confidence: 89%
“…SDSS J0924 is another new discovery from the SDSS survey, identified by Szkody et al (2005) due to a spectrum which shows strong and narrow Balmer emission and hints of the secondary star towards the red end. The presence of strong He ii is indicative of a magnetic system, but polarimetric observations revealed no polarisation.…”
Section: Sdss J09244448+0801509mentioning
confidence: 99%
See 1 more Smart Citation
“…Szkody et al (2002Szkody et al ( , 2003Szkody et al ( , 2004Szkody et al ( , 2005Szkody et al ( , 2006Szkody et al ( , 2007Szkody et al ( , 2009Szkody et al ( , 2011) produced a catalogue of 285 CVs identified in this way. The Quasar Survey is estimated to be 95 per cent complete down to i < 19.1 (Vanden Berk et al 2005;Richards et al 2006).…”
Section: The Sdss CV Samplementioning
confidence: 99%
“…SDSS J0039 was discovered to be a CV by Szkody et al (2005) on the basis of an SDSS spectrum which shows Balmer and He I emission lines. Very broad absorption is visible around the higher-order Balmer lines, indicating that the WD emits a large fraction of the overall light of the system.…”
Section: Introductionmentioning
confidence: 99%